Comparative analysis of chicken and guinea fowl egg powder - Olugbemi, T.S.; Liman, J.; Daramola, E.I; Oyeniran, A.D.; Muhammad, A.A.` (Nigerian Journal of Animal Science, 2023)
The objective of this study was to comparatively evaluate egg powders produced from fresh chicken egg (CEP) and Guinea fowl egg (GEP) with a view of determining the suitability of Guinea fowl egg as a possible alternative to that of chicken. The CEP and GEP were made by dehydrating 35 and 34 fresh Chicken and Guinea fowl eggs respectively separately using a dehydrator and smoothly blending the resultant egg crusts. Samples from the CEP and GEP were analyzed for their proximate and mineral composition. An organoleptic assessment using ungarnished and garnished fried CEP and GEP was also conducted. The yield percentage obtained from the Chicken and Guinea fowl eggs were 22.4%, and 28.4% respectively. The proximate composition showed the CEP to be higher in crude protein (46.8%) and moisture (6.20%), than the GEP (42.4% crude protein and 2.10% moisture). The ash and oil percentage of the GEP (5.50% and 35.9%) were higher than that of the CEP (3.75% and 29.9%) respectively. The composition of Ca, Mg, K, Fe, Zn and Mn were highest in CEP while GEP had the highest P and Cu. Fried guinea fowl eggs whether ungarnished or garnished were rated better (P<0.05) in most of the organoleptic indices. It can be concluded that egg powder can be produced from guinea fowl eggs and it gives higher yield than chicken eggs. The guinea fowl egg powder can also be used comparatively to that of the chicken egg in frying, pastries and other confectioneries irrespective of their proximate and mineral variance.